2017
DOI: 10.1007/s13201-017-0619-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of roadside surface water quality of Savar, Dhaka, Bangladesh using GIS and multivariate statistical techniques

Abstract: In this study, multivariate statistical techniques in collaboration with GIS are used to assess the roadside surface water quality of Savar region. Nineteen water samples were collected in dry season and 15 water quality parameters including TSS, TDS, pH, DO, BOD, Cl -, F -, NO 3 2-, NO 2 -, SO 4 2-, Ca, Mg, K, Zn and Pb were measured. The univariate overview of water quality parameters are TSS 25.154 ± 8.674 mg/l, TDS 840.400 ± 311.081 mg/l, pH 7.574 ± 0.256 pH unit, DO 4.544 ± 0.933 mg/l, BOD 0.758 ± 0.179 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…However, for testing water from more contaminated sources, as determined by multivariate analysis of environmental factors where the industrial waste disposal and high population density matters [81,82], further treatment of the sample to remove inhibitors may be required. A study on water quality assessment of the roadside surface of Savar, Dhaka explained the impact of vehicle emission, atmospheric deposition from brick field, industrial pollution and massive urbanization on the water reservoirs as total suspended solids (>25 mg/L), total dissolved solids (>840mg/L), biological oxygen demands (0.758 mg/L), dissolved oxygen (4.5 mg/L) were high or even higher than the standards [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for testing water from more contaminated sources, as determined by multivariate analysis of environmental factors where the industrial waste disposal and high population density matters [81,82], further treatment of the sample to remove inhibitors may be required. A study on water quality assessment of the roadside surface of Savar, Dhaka explained the impact of vehicle emission, atmospheric deposition from brick field, industrial pollution and massive urbanization on the water reservoirs as total suspended solids (>25 mg/L), total dissolved solids (>840mg/L), biological oxygen demands (0.758 mg/L), dissolved oxygen (4.5 mg/L) were high or even higher than the standards [72].…”
Section: Discussionmentioning
confidence: 99%
“…As proof of concept, we analyzed water samples collected from the river basin of the Turag River in a region endemic for cholera, the Gabtoli area of Dhaka, Bangladesh. Approximately 25,000 people live in this area, which is surrounded by brickfields with high traffic [72]. This site was chosen as previous studies indicated the presence of V. cholerae O1 and cholera infections are often detected in people living in the surrounding area [73].…”
Section: Discussionmentioning
confidence: 99%
“…As proof of the concept, we analyzed water samples collected from the river basin of the Turag River in a region endemic for cholera, the Gabtoli area of Dhaka, Bangladesh. Approximately 25,000 people live in this area, which is surrounded by brickfields with high traffic [ 76 ]. This site was chosen because previous studies indicated the presence of V. cholerae O1 and cholera infections in people living in the surrounding area [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for testing water from more contaminated sources, as determined by multivariate analysis of environmental factors where the industrial waste disposal and high population density matters [ 85 , 86 ], further treatment of the sample to remove inhibitors may be required. A study on water quality assessment of the roadside surface of Savar, Dhaka explained the impact of vehicle emission, atmospheric deposition from brick fields, industrial pollution and massive urbanization on the water reservoirs; total suspended solids (>25 mg/L), total dissolved solids (>840 mg/L), biological oxygen demands (0.758 mg/L) and dissolved oxygen (4.5 mg/L) were high or even higher than the standards [ 76 ]. Another potential limitation of our assay would be a discrepancy in genome copy numbers per cell between the standard and the samples.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of human activities causes re-distribution of heavy metals in a specific space. The types of pollution sources can be preliminarily judged and screened via analyzing the distribution pattern of heavy metal pollution [ 12 ]. In the analysis of pollution sources, multivariate statistical analysis is mainly conducted through analyzing the data to find out its internal laws, and, then, finding the main pollution factors.…”
Section: Introductionmentioning
confidence: 99%